Interactive maps of drought risk areas for efficient targeting of CSA and CIS packages - Mathieu, Renaud; Yeggina, Pavan Kumar; Teja, Charan; Murugesan, Deiveegan; Akpoffo, Marius; Dossou-Yovo, Elliott Ronald; Gatti, Luca (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Droughts are common in Mali and have a significant impact on agricultural and water resources. However, there has been no previous evaluation of agricultural drought risk in Mali. A comprehensive agricultural drought risk assessment approach that considers drought severity, location, timing, and duration of drought occurrences was used to create detailed drought risk information for operational drought management in Mali. The study was carried out in the Sikasso and Segou regions, which are key agricultural production areas in Mali. Four unique zones were defined in the study area based on yearly mean rainfall data from 2017 to 2022, and a reference line was constructed for each zone. The reference line was utilized to determine the deviation of EDPSVI. Fortnightly drought indicators from the Senitnel-1 SAR-based biomass EDPSVI time series were successfully constructed, and frequency was computed annually for each year from 2017 to 2022 using seasonal intensity data cubes at 250 m resolution. This provides a thorough overview of drought conditions as well as quantitative assessments of drought severity, location, timing, and duration. These data can be utilized to disseminate drought-tolerant varieties and resilient technologies throughout Mali's most drought-affected regions.